Global Value Chains Industri Kopi di Provinsi Bali - I Putu Krisna Yudiana; I Gusti Agung Ayu Apsari Anandari (Lembaga Pengembangan Kinerja Dosen, 2026)
This study maps and analyzes the Global Value Chains (GVC) of Bali’s coffee industry using a descriptive qualitative design based on in-depth interviews with farmers, collectors, and roasteries in Tabanan, Buleleng, and Bangli, complemented by field observations. The Miles–Huberman–Saldaña interactive approach guides data reduction, display, and verification. Findings indicate a value chain dominated by smallholders with limited landholdings, a local market structure tending toward monopsony, and post-harvest infrastructure gaps that incentivize sales as red cherries (≈IDR 11,000/kg). Substantial value is captured downstream green beans (≈IDR 80,000–85,000/kg) and roasted beans (≈IDR 85,000–120,000/kg) primarily by collectors/roasteries with superior access to information, technology, and markets. Exports to China, the United States, Taiwan, and South Korea occur sporadically due to complex licensing procedures. The Geographical Indication Protection Society (MPIG) helps safeguard quality and origin, yet its price-setting influence warrants caution to ensure broad, equitable benefits. The study underscores information asymmetries and market access barriers that weaken farmers’ bargaining power and constrain value distribution upstream. Policy recommendations include strengthening cooperatives/marketing partnerships, investing in post-harvest technology and quality assurance (e.g., cupping scores/GI), improving price transparency through market information systems, and streamlining export regulations. The results contribute to GVC governance insights for Bali coffee and outline an agenda to enhance value added, sustainability, and smallholder welfare.